La ayuda para el comercio, sus límites y desafíos - Peixoto Batista, Juliana; Knoop, Vanesa (Latin American Journal of Trade Policy, 2022)
Aid for trade (AfT), as initiative, is quite recent, although it has been a part of the multilateral trade system from its very beginning. After increasing claims of an asymmetric system by developing countries and promises of mainstreaming development in the WTO, the “Aid for Trade” concept has been created, and a specific initiative was launched. As of today, this global initiative faces many challenges, and the politics of international development conducted by different international agencies also reflects the implementation of the initiative. The loss of strength of the multilateral system has also given way to think about this initiative from different perspectives such as South-South cooperation and regional integration. The objective of this article is to analyze the AfT initiative, its origins, its challenges and future, in a changing world where pandemic still threats development goals.